2009
DOI: 10.1086/599313
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative HIV Viremia during Highly Active Antiretroviral Therapy Is a Strong Predictorof AIDS‐Related Lymphoma

Abstract: Cumulative HIV viremia is an independent and strong predictor of AIDS-related lymphoma among patients receiving HAART. The influence of cumulative HIV viremia may differ between lymphoma subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
108
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(123 citation statements)
references
References 25 publications
14
108
0
1
Order By: Relevance
“…122 A total of 25 consecutive patients with pulmonary tuberculoma were enrolled. PET/CT imaging was performed 60 (range [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] 120 Also, %Delta SUV max proved higher in this series when compared with the findings by Kim et al 122 (mean: 35, range: 23-54). From a clinical point of view, the high SUV values and the SUV increase over time observed are of concern when considering the specificity of cancer diagnosis in patients with solitary lung nodules.…”
Section: Pulmonarymentioning
confidence: 55%
“…122 A total of 25 consecutive patients with pulmonary tuberculoma were enrolled. PET/CT imaging was performed 60 (range [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] 120 Also, %Delta SUV max proved higher in this series when compared with the findings by Kim et al 122 (mean: 35, range: 23-54). From a clinical point of view, the high SUV values and the SUV increase over time observed are of concern when considering the specificity of cancer diagnosis in patients with solitary lung nodules.…”
Section: Pulmonarymentioning
confidence: 55%
“…In addition to its effects on B cells, p17 can induce angiogenesis/lymphangiogenesis in vitro and in vivo (20)(21)(22). In addition, cumulative viremia during cART is known to be a strong predictor of HIV-NHL, especially for BL (23). Thus, these findings support the hypothesis that HIV proteins may directly contribute to lymphomagenesis.…”
Section: Significancementioning
confidence: 54%
“…Early studies suggested that nadir (lowest ever) CD4þ lymphocyte count was an important predictor of acquired immunodeficiency syndrome related to non-Hodgkin lymphoma (AIDS-NHL) (Ambinder et al 2010). Two recent studies reported that the most recent CD4þ lymphocyte count, rather than the nadir lymphocyte count, is predictive of AIDS-NHL (Bower et al 2009;Zoufaly et al 2009 Figure 1. The ''meet in the middle approach'' concept.…”
Section: Lymphoma Blood Biomarkers Among Hiv Patientsmentioning
confidence: 99%
“…The ''meet in the middle approach'' concept. (Zoufaly et al 2009;Engels et al 2010). HIV virions that carry the CD40 ligand, an activator of induced cytidine deaminase (AID), might stimulate polyclonal B cell activation and generate the molecular lesions that contribute to the development of NHL (Ambinder et al 2010).…”
Section: Lymphoma Blood Biomarkers Among Hiv Patientsmentioning
confidence: 99%